Reciprocal ECG change in reperfused ST-elevation myocardial infarction is associated with myocardial salvage and area at risk assessed by cardiovascular magnetic resonance. Issue 22 (7th September 2013) - Kidambi, Ananth; Mather, Adam N; Uddin, Akhlaque; Motwani, Manish; Ripley, David P; Herzog, Bernhard A; McDiarmid, Adam; Gunn, Julian; Plein, Sven; Greenwood, John P
Abstract : Objective: ST-elevation acute myocardial infarction (STEMI) is frequently associated with reciprocal ST depression in contralateral ECG leads. The relevance of these changes is debated. This study examined whether reciprocal ECG changes in STEMI reflect larger myocardial area at risk (AAR) and/or infarct size. Design: Patients were stratified by presence of reciprocal change on the presenting ECG, defined as ≥1 mm ST depression in ≥2 inferior leads for anterior STEMI, or ≥2 anterior leads for inferior STEMI. Infarcted tissue was defined on late enhancement and AAR on T2-weighted cardiovascular magnetic resonance (CMR). Setting: Patients with reperfused first STEMI underwent CMR within 3 days of presentation. Main outcome measures: In addition to AAR and infarct mass, myocardial salvage was calculated as (AAR mass—infarct mass) and salvage index as myocardial salvage/AAR mass. Results: Thirty-five patients were analysed (n=35). Patients with reciprocal ECG changes (n=19) had higher AAR mass than those without (42 g vs 29 g, p<0.001), and higher myocardial salvage (27 g vs 9 g, p<0.001) and myocardial salvage index (61% vs 17%, p<0.001) but similar infarct size (16 g vs 20 g, p=0.3) and ejection fraction (43% vs 45%, p=0.5). Conclusions: STEMI patients with reciprocal ECG changes have larger AAR, higher myocardial salvage and salvage index than those without. Reciprocal changes appear to be a marker of increased ischaemic myocardium at risk and indicate the potential for increased salvage with emergency revascularisation. Reciprocal changes showed no relationship to infarct size, which may be influenced by ischaemia time and other treatment factors.